Britannica Concise Encyclopedia. (1st ed.) (Encyclopædia Britannica, 2020)
One-volume, condensed version of the 32-volume Encyclopaedia Britannica, includes about 28,000 clearly written entries covering various branches of human knowledge, such as science, history, business, art, culture, geography, and geology, as well as more contemporary issues, such as cloning, terrorism, and globalization.